Hydrogen Index determination for the well-log ES-1 drilled at the Espírito Santo basin (western South Atlantic) for the Late Cretaceous - Santos, Thiago Pereira dos; Bione, Fellippe Roberto Alves; Venancio, Igor Martins; Bernardes, M C; Belem, Andre L; Lisboa, Luana P; Franco, Daniel R; Díaz, Rut A; Moreira, Manuel; Leonardo, Noele F; Souza, Igor V; Spigolon, André L D; et al. (In: Santos, TP et al. (2022): Late Cretaceous cyclostratigraphy for the subtropical western South Atlantic, Espírito Santo Basin [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.944599, 2022)
HI derives from Rock-Eval pyrolysis using 100 mg of grounded and powdered rock within a Rock-Eval 6 device.
Keywords: Late Cretaceous; Milankovitch forcing; orbital tuning; South Atlantic